Minutes of the 45th Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 44th Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 44th Meeting of the Academic Council. 3. Approval of the results of the students graduating at the end of Fall-2011 Semester. 4. Progress of the 7th Convocation. 5. Miscellaneous: 5.1 Admission Test. 5.2 Continuation of Studies beyond 3rd times probation. 5.3 Appeal seeking withdrawal of expulsion order and continuation of study in BRAC University.